FREYCINETIA OF MOUNT NYIUT AND PALUNG, WEST KALIMANTAN BASED ON LEAF ANATOMICAL CHARACTERS - Rizki, Fitri Sri; Chikmawati, Tatik; ., Rugayah (Perhimpunan Biologi Indonesia, 2015)
Freycinetia Gaudich. is a climber plant belongs to the family of Pandanaceae. Seven species of Freycinetia from Mount of Nyiut and Palung located in West Kalimantan have been recognized based on leaf anatomy. Paradermal and transversal leaf sections of those species were observed, and the data was used to construct a dendrogram using Jaccard similarity index and Unweighted Pair Group Method with Arithmetic Average (UPGMA) method. Six main characters have been used to distingush and evaluate the similarity between its, i.e. number of hypodermal layers, number of palisade layers, shape of sponge tissue, layout of sclerenchyma tissue, stomata size, presence of costal and intercostal cells, and shape of vascular bundle. Cluster analysis based on the anatomical data showed that seven Freycinetia species were clustered into two major groups at similarity coefficient 0.38. The first group consisted of F. angustifolia, F. imbricata, F. sarawakensis, and F. winkleriana, while the second group consisted of F. corneri, F. sessiliflora and F. sumatrana. Keywords: Anatomical variation, Freycinetia, West Kalimantan